1991
DOI: 10.1111/j.1365-3040.1991.tb00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface potentials and hydraulic signals in wheat leaves following localized wounding by heat

Abstract: Abstract. Localized burning of a leaf causes a rapid change in apoplastic electrical potential throughout the shoot of wheat seedlings (‘variation potential’). It also causes marked increases in turgor pressure in epidermal cells of adjoining leaves. These turgor increases indicate rapid propagation throughout the seedling, of a hydraulic pressure wave from the site of wounding. Evidence is presented that this pressure wave is caused by relief of xylem tension, by water released from damaged cells in the wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 24 publications
2
78
0
Order By: Relevance
“…Several hypotheses are currently considered in the literature (Malone & Alarcon 1995): phloem transport of proteinase-inhibitor inducing factors (PIIF; Pearce et al 1991), hydraulic dispersal of PIIF chemicals by mass flow in the xylem (Malone 1993(Malone , 1994, and electrical transmission (Williams & Pickard 1972;Roblin & Bonnemain 1979, 1985Satter 1990;Fromm 1991;Sibaoka 1991;Wildon et al 1992). Our results suggest that (1) an intricate relationship between electrical and hydraulic signals frequently exists (see also Malone & Stankovic 1991;Stahlberg & Cosgrove 1997) and that (2) other mechanisms for transmission of electrical signals must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses are currently considered in the literature (Malone & Alarcon 1995): phloem transport of proteinase-inhibitor inducing factors (PIIF; Pearce et al 1991), hydraulic dispersal of PIIF chemicals by mass flow in the xylem (Malone 1993(Malone , 1994, and electrical transmission (Williams & Pickard 1972;Roblin & Bonnemain 1979, 1985Satter 1990;Fromm 1991;Sibaoka 1991;Wildon et al 1992). Our results suggest that (1) an intricate relationship between electrical and hydraulic signals frequently exists (see also Malone & Stankovic 1991;Stahlberg & Cosgrove 1997) and that (2) other mechanisms for transmission of electrical signals must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…External nitrate and ammonium induced inverse effects on the cortical membrane potential and the TRP, but no short-term effect on xylem pressure. It is important to note that the xylem pressure was not affected, since hydraulic changes and changes in volume flow have repeatedly been shown to affect electrical gradients in higher plants (Malone & Stankovic 1991;Boari & Malone 1993;Wegner & Zimmermann 1998), for example, due to the induction of streaming potentials. Addition of nitrate to the medium always resulted in a concentration-dependent hyperpolarization of the membrane potential of the cortex cells of 'low-salt' plants.…”
Section: Discussionmentioning
confidence: 99%
“…This VP (or SW) is not a genuine electrical signal in so far as its method of propagation is still unknown. It appears to be the consequence of the prior passage of a hydraulic signal [9,12,30]. Thus, it is a VP rather than an AP that evokes calmodulin transcript accumulation at a distance followed by the inhibition of growth in Bidens.…”
Section: Controlmentioning
confidence: 99%
“…Three different hypothesis have been proposed to explain long-distance information transfer: (i) it has been suggested that a mobile chemical signal is the causal agent and candidates such as oligosaccharides [4], abscisic acid [5] and systemin [6] have been proposed; (ii) it has also been shown that one response to external stimuli in higher plants is the elicitation and the spreading of a variation in the transmembrane electrical potential and several authors suggested that these electrical signals could be the 'information' carrier [1,3,7,8]; (iii) it has been demonstrated that hydraulic signals are transmitted from damaged tissue [9,10] and it has been proposed that hydraulic signals could form part of a widespread mechanism for coordination of plant responses [11].…”
Section: Introductionmentioning
confidence: 99%